Effects of Different Bio-Rational Compounds on Mortality of Diamond Back Moth (Plutella xylostella L.) Larva under Laboratory Condition - Bhattarai, A.M.; Tiwari, S. (Journal of Agriculture and Environment, 2021)
A leaf dip technique of bioassay for mortality of DBM larvae was conducted in laboratory condition with room temperature of 25±2°C, relative humidity of 80±3% and 13:11 ratio of Light: dark period at Department of Entomology, Agriculture and Forestry University, Rampur, Chitwan with three replication and eight treatments; i.e. i) Lipel (Bacillus thuriengiensis var. kursataki) 2gm/l, ii) Racer (Beauveria bassiana 1.15% WP) 2gm/l, iii) Derisom (Fractions of Derris indica) 2ml/l, iv) Anosom (Extracts of Annona spp. 1%) 2ml/l, v) Neemix (Neem oil 60% w/w, Azadiractin content less than 300 ppm) 2ml/l, vi) Anthsuper (Chloropyrifos 16% A.I. + Alphacypermethrin 1%EC (w/w) 2ml/l, vii) cow urine (1:5 with water) and viii) control (water spray) in Completely Randomized Design (CRD). The larval mortality was taken after 3, 9, 21, 33, 57 and 93 hours after the treatment application. The larval mortality was found to be significantly higher in Anthsuper treated with 100% mortality of larvae within 33 hours after treatment application followed by cow urine, botanicals (Neemix, Derisom and Anosom) and microbials (Racer and Lipel) where the larval mortality over control was found to ranging from 10% to 47.57% during the experimental period. The larval mortality was 47.57% for Cow urine and Neemix followed by 38.14% for Anosom, 33.29% for Racer, 28.57% for Derisom and 19% for Lipel.it is concluded that chemical pesticide Anthsuper is superior for immediate control of the pest but considering the safety of environment and human health; for long-term control of the pest botanicals and microbials would be more efficient.